2021
DOI: 10.1002/adfm.202105719
|View full text |Cite
|
Sign up to set email alerts
|

Solution‐Processable Carbon Nanotube Nanohybrids for Multiplexed Photoresponsive Devices

Abstract: Here, the formation of carbon nanotube (CNT)-based nanohybrids in aqueous solution is reported, where DNA-wrapped CNTs (DNA-CNTs) act as templates for the growth of PbS and CdS nanocrystals, toward the formation of PbS-DNA-CNT and CdS-DNA-CNT heterostructures. Solution-processed multiplexed photoresponsive devices are fabricated from these nanohybrids, displaying a sensitivity to a broad range of illumination wavelengths (405, 532, and 650 nm). The DNA-CNT and CdS-DNA-CNT devices show a drop in the current whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…The response time of paper-based PD holds significant importance as it directly detects the changes in incident light intensity accurately and quickly. Herein, we have explored different routes for the enhancement of response time in paper-based PD [119][120][121]. For instance, (a) material optimization plays an important role to improve the response time.…”
Section: Different Route For Enhancement Of Response Time Of Paper-ba...mentioning
confidence: 99%
“…The response time of paper-based PD holds significant importance as it directly detects the changes in incident light intensity accurately and quickly. Herein, we have explored different routes for the enhancement of response time in paper-based PD [119][120][121]. For instance, (a) material optimization plays an important role to improve the response time.…”
Section: Different Route For Enhancement Of Response Time Of Paper-ba...mentioning
confidence: 99%
“…Researchers often use hybridization to create many materials with specific properties and functions. Because of these properties, these hybrid materials are usually used for catalysts, [177][178][179] photoresponsive devices, [180] electrochromic devices, [176] organic thermoelectric devices. [181,182] The idea of using these hybridized materials for MAs has also been considered by researchers who have discovered that some of these hybridized materials have a powerful ability to capture light, which led to the emergence of MAs using hybrid materials, [183][184][185][186] and through the unremitting efforts of researchers, many BMAs using hybrid materials have been successfully designed, [126,187,140] which have contributed significantly to the development and applications of BMAs.…”
Section: Light Capture By Hybridized Materialsmentioning
confidence: 99%
“…In 2009, Peng et al proposed a FET fabricated with ACdielectrophoresis (AC-DEP) aligned SWCNTs between Ti/Au contacts on a SiO 2 (200 nm)/Si wafer, [142] a technique often proposed for the manufacturing of an aligned array of CNTs. [143][144][145][146] Authors suggested the Schottky behavior of the CNT/metal junction. 500 nm thick Si 3 N 4 passivation layer was deposited by plasma enhanced CVD (PE-CVD) to fabricate FP, NP, CE, and JE -FETs.…”
Section: The Role Of the Cnt/metal Junctionmentioning
confidence: 99%